Paremiological Units - as a Special Type of Phraseological Units with a Sentence Structure (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
. In this article  Paremiological units are analyzed as a special type of phraseological units with sentence structure. Paremas are the object of study of literary studies because they are passed down from generation to generation only orally, they are a product of folk art, because most of them are often similar to poetic form and they use a number of figurative tools such as simile, antithesis, anaphora, alliteration, irony, pitch. At the same time, paremas are also an object of study of linguistics, as they are made up of words and consist of sentences expressing a certain idea.